Neuralink’s Brain-Computer Interfaces and the Reshaping of Religious-Psychological Experience - Alkhouri, Khader I. (Conatus - Journal of Philosophy, 2025)
This research article examines the profound implications of Neuralink’s brain-computer interface (BCI) technology on religious and psychological experiences. As BCIs advance toward direct neural interfacing, they present unprecedented opportunities and challenges for human spirituality, cognition, and self-understanding. Drawing on interdisciplinary research, we investigate the potential for technologically-mediated spiritual experiences and their impact on traditional religious practices and institutions. The study explores ethical considerations surrounding cognitive liberty, mental privacy, and the authenticity of BCI-induced experiences. Key findings indicate that BCIs could potentially induce or enhance altered states of consciousness associated with spiritual experiences, augment meditation practices, and redefine religious rituals. However, these capabilities raise significant ethical concerns, including issues of cognitive manipulation and equitable access. The research also highlights potential shifts in religious authority structures and the emergence of new techno-spiritual philosophies. By analyzing the societal and cultural impacts of widespread BCI adoption, this study provides a nuanced understanding of how Neuralink’s technology may reshape the landscape of human consciousness and spirituality. The article contributes to the critical dialogue on the future of religious and psychological experiences in an era of advancing neurotechnology, balancing the transformative potential of BCIs with careful consideration of their ethical implications and philosophical ramifications.